Comparative Public Management : Why National, Environmental, and Organizational Context Matters - Avellaneda, Claudia N.; Rutherford, Amanda; Meier, Kenneth J., 1950- (Book collections on Project MUSE., 2017)
The field of public management has become increasingly international, but research and policy recommendations that work for one country often do not work in another. Why, for example, is managerial networking important in the United States, moderately effective in the United Kingdom, and of little consequence in the Netherlands? This text argues that scholars must find a better way to account for political, environmental, and organizational contexts to build a more general model of public management. The volume editors propose a framework where context influences the types of managerial actions that can be used effectively in public organizations. After introducing this framework, the book offers seven empirical chapters - cases from seven countries and a range of policy areas (health, education, taxation, and local governance) - showing how management affects performance in different contexts. Following these empirical tests, the book examines themes that emerge across cases and seeks to set an agenda for continued research.